نفي الاحتلال الفرنسي لمحمد بن محمود بن العنّابي - بن بردي الزبير; زقب عثمان (University of Eloued جامعة الوادي, 2024)
يعتبر النّفي من أبرز وأخطر السياسات التي طبّقتها إدارة الاحتلال الفرنسي في حقّ مئات الجزائريين، لتحطيم معنوياتهم والقضاء على الرّوح الوطنية وعلى شوكة المقاومة ضدّ وجود المحتل. ومن أوائل من شملهم النّفي إلى خارج البلاد: مجموعة من نُخب وأعيان مدينة الجزائر تخندقوا في صفوف المعارضة والمقاومة السياسية والفكرية ضدّ المحتل الفرنسي وسياساته. وفي هذا السّياق يندرج مقالنا عن أحد أبرز هذه النّخب، هو المفتي الحنفي محمد بن محمود ابن العنّابي، وهذا من خلال التطرّق إلى أحد أهمّ محطّات حياته، وهو نفيه خارج البلاد. فبعد نشاطه السياسي والفكري المتنامي ضدّ الاحتلال الفرنسي، قرّر الجنرال كلوزيل وضع حدٍّ له ونفيه إلى الإسكندرية بمصر التي اختارها مأوى له. Exile is the most prominent and dangerous policies applied by the French conquest leaders against hundreds of Algerians, to break their morale and weaken national spirits and the thorns of resistance against their existence. One of the first to be exiled outside the country: a group of elites and rebells from Algiers who have been throttled into opposition, political and intellectual resistance against the French conquerors existence and policies. In this context, our article on one of the most prominent elites is Mufti Hanafi Mohamed ben Mahmoud ben Al-Annabi, and this is by touching on one of the most important points of his life, his exile outside the country. After his growing political and intellectual activity against the French conquest, General Clauzel decided to put an end to him and deny him to Alexandria, Egypt, which he chose as his home.
Keywords: النّفي; كلوزيل; ابن العنّابي; الاحتلال; المفتي; Exile; Clauzel; Ibn Al-Annabi; Occupation; Mufti